2022
DOI: 10.1002/agj2.20982
|View full text |Cite
|
Sign up to set email alerts
|

Tea plant growth and soil nutrients in response to the application of fertilizer in Guizhou province, China

Abstract: More than half of the total production of tea [Camellia sinensis (L.) Kuntze] in China is produced in the Guizhou province. However, in this region soils generally have low soil fertility, so new techniques to improve the productivity and fertility are needed. The aim of this study was to evaluate the effects of application of seven types of humic acid‐based organic–inorganic compound fertilizer (HTOF) on tea quality and productivity. Two different cultivars of tea (cultivars Shiqiantaicha and Fudingdabaicha) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…Another study showed that humic acid‐based organic‐inorganic compound fertilizer applied to low fertility soils improved soil characteristics and plant growth of tea plantations (Sui et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Another study showed that humic acid‐based organic‐inorganic compound fertilizer applied to low fertility soils improved soil characteristics and plant growth of tea plantations (Sui et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Currently, the forms of fertilizer used in tea gardens are becoming increasingly diverse, including organic manures [20,21], rapeseed cake [6], and chemical fertilizers [22]. However, all these fertilizers are applied through ditching manually [23]. Compared to traditional fertilization methods, drip fertilization systems have been repeatedly proven to be beneficial for forming a good root structure, improving crop yield and quality, and reducing environmental risks [24].…”
Section: Introductionmentioning
confidence: 99%